Understanding new expectations for democratic environmental governance - Belly-le Guilloux, Léna (2021)
This paper is based at the nodal points of several phenomena, including political distrust in France, a European trend supporting public participation, a failed experiment of citizen assembly in France, and the organisation of a citizen collective to advocate for a replication of a similar citizen assembly, at the regional level, by environmental activists. In this context, I have conducted a policy analysis focusing particularly on the activist movement with the aim to provide insights into new expectations for democratic governance of environmental resources.